Study of [chi] b meson production in pp collisions at √s=7and 8TeV and observation of the decay [chi] b (3P) → [upsilon] (3S)γ - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; Gersabeck, Evelina; et al. (The European physical journal. C, Particles and fields, 2014)
A study of χb meson production at LHCb is performed on proton–proton collision data, corresponding to 3.0 fb−1of integrated luminosity collected at centre-of-mass energies s√ = 7 and 8 TeV. The fraction of Υ(nS) mesons originating from χb decays is measured as a function of the Υ transverse momentum in the rapidity range 2.0<yΥ<4.5. The radiative transition of the χb(3P) meson to Υ(3S) is observed for the first time. The χb1(3P) mass is determined to be mχb1(3P)=10511.3±1.7±2.5MeV/c2, where the first uncertainty is statistical and the second is systematic.